Peak car use - what does it mean for urban design and planning? - Newman, Peter (2012)
The trends in urban car use are now demonstrating a new phenomenon where a peak has occurred and rapid declines are setting in. Some of the causes of peak car use are suggested, but more importantly the need for urban design and planning to change their practice is suggested. This should include: first, not increasing road capacity and using the road space freed up for sustainable transport improvements, especially walkability; second, planning for 50% reductions in cars with all the growth being electric vehicles; third, ensuring quality electric transit is the key facilitator of further urban growth and is tied into it through value capture; and fourth, facilitating green urban renewal as the main game in urban planning to achieve the polycentric city.